Semi-circular compact CPW-fed antenna for ultra-wideband applications - Farhad E. Mahmood; Saad Wasmi Osman Luhaib (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
This paper presents a simple structure and small size antenna design with dimensions of 43×47 mm2 to perform an ultra-wideband (UWB) frequency range using a semicircular co-planar waveguide (CPW). This antenna has been designed and simulated by the computer simulation technology (CST) microwave studio suit. In this work, we design an ultra-wideband antenna (about 2 GHz to 10 GHz) by feeding a semi-circular compact antenna via a co-planar waveguide for input impedance of 50 Ω. The CST simulation results show that our designed antenna has a very good impedance and radiation characteristic within the intended ultra-wideband. Because of the small size and the suitable shape, this antenna can be used in many wireless communication applications, such as a radio frequency identifier (RFID), indoor wireless local area network or wireless fidelity (WiFi), internet of things (IoT), millimeter waves communications (mmWave), global positioning system (GPS), and many applications of 6G systems.